2015
DOI: 10.1016/j.ajhg.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Decoding NF1 Intragenic Copy-Number Variations

Abstract: Genomic rearrangements can cause both Mendelian and complex disorders. Currently, several major mechanisms causing genomic rearrangements, such as non-allelic homologous recombination (NAHR), non-homologous end joining (NHEJ), fork stalling and template switching (FoSTeS), and microhomology-mediated break-induced replication (MMBIR), have been proposed. However, to what extent these mechanisms contribute to gene-specific pathogenic copy-number variations (CNVs) remains understudied. Furthermore, few studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 71 publications
2
23
0
1
Order By: Relevance
“…[5][6][7][8][9][10] Although we cannot completely rule out the possibility of two independent two-step events, we suggest that both aberrations can be traced back to a shared primary Alu retrotransposition event. This interpretation is based on (i) identity of the region harboring the presumed integration; (ii) involvement of AluYb8 as one of the most active Alu subfamilies; 16 (iii) presence of a classical L1-endonuclease site; 16 (iv) the sequence representing the potential target site duplication to be of the typical size of 16 bp; 16 and (v) the rarity of the haplotype on which both variants reside.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10] Although we cannot completely rule out the possibility of two independent two-step events, we suggest that both aberrations can be traced back to a shared primary Alu retrotransposition event. This interpretation is based on (i) identity of the region harboring the presumed integration; (ii) involvement of AluYb8 as one of the most active Alu subfamilies; 16 (iii) presence of a classical L1-endonuclease site; 16 (iv) the sequence representing the potential target site duplication to be of the typical size of 16 bp; 16 and (v) the rarity of the haplotype on which both variants reside.…”
Section: Discussionmentioning
confidence: 99%
“…4 Meanwhile, a few disease-associated deletions that harbor Aluderived sequence insertions have been reported, including in the BRCA-1, CHD7, NF1, PMM2, GLA, and LPL genes. [5][6][7][8][9][10] Mechanistic interpretations referred to the one-step AMD concept, 8 or alternatively suggested a two-step scenario in which an Alu insertion precedes the actual deletion event. 10 The present study reports on the characterization of two distinct Alu insertion-associated deletions in the SPAST gene, alterations of which cause hereditary spastic paraplegia type SPG4 (OMIM 604277).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,9,43,44 Analyses of the breakpoints of these deletions show that all of them involve Alu elements suggesting that they were mainly generated by NAHR (Supplementary Table S8). Still, as a recent study on the genetic mechanisms responsible for intragenic gross deletions inactivating the NF1 gene suggests that FoSTeS/MMBIR is an underestimated cause of this type of gene alterations, 22 it may be worthwhile to test whether also RBM may have a role for the high frequency of non-recurrent (intragenic) deletions affecting the PMS2 gene.…”
Section: Resultsmentioning
confidence: 98%
“…18,20,21 Up to now, complex PMS2 alterations thought to result from RBM have not been described, but analysis of rearrangements in other genes has shown that RBMs are probably still under-recognised as molecular mechanism underlying (mainly complex) genomic, genic and exonic rearrangements. 18,22 Here, we describe a chromosomal rearrangement inactivating the PMS2 gene in an individual with CMMRD syndrome. Thorough characterisation of this complex rearrangement involving sequences of the inverted 100-kb LCR and a human endogenous retrovirus (HERV) element on 7p22.1 renders strong evidence that it results from a RBM.…”
Section: Introductionmentioning
confidence: 96%